A fossil heron from the early Oligocene of Belgium: the earliest temporally well‐constrained record of the Ardeidae. (6th April 2018) - Mayr, Gerald; De Pietri, Vanesa L.; Scofield, Richard Paul; Smith, Thierry
Abstract : We describe the earliest temporally well‐constrained fossil that can be assigned to the Ardeidae (herons), from the lowermost Oligocene (32.0–33.0 million years ago) of Belgium. The specimen, a partial tarsometatarsus, belongs to a small species and is described as Proardea ? deschutteri n. sp. It exhibits the characteristic tarsometatarsus morphology found in extant heron species, but a confident assignment to one of the ardeid subclades is not possible and even the assignment of the new fossil species to the crown group (the clade including the extant species) cannot be established. The fossil indicates a divergence of herons from their sister taxon by at least the earliest Oligocene, and current paleontological data suggest that herons arrived in Europe shortly after a major faunal turnover at the Eocene/Oligocene boundary. We consider that dispersal is the likely reason for the sudden appearance of herons in the earliest Oligocene of Europe but it is uncertain from where exactly this took place, with Asia and Africa being among the candidate areas.